STIMULASI PERTUMBUHAN Dendrobium sp MENGGUNAKAN HORMON AUKSIN Naphtalena Acetic Acid (NAA) DAN Indole Butyric Acid (IBA) - Astutik Astutik; Astri Sumiati; Sutoyo Sutoyo (BUANA SAINS, 2021)
Dendrobium sp is one type of orchid that is in demand by the public because of the various flower shapes and attractive colors but has a long growth period. Therefore, efforts are needed to accelerate the flowering phase of Dendrobium sp. The purpose of this study was to determine the effect of the hormone auxin in accelerating the growth of Dendrobium sp. The research was carried out using a completely randomized design with a 4x2 factorial pattern with 3 replications. The first factor was the treatment of hormone Auxin NAA (A1) and IBA (A2) then the concentration consisted of 4 levels, namely control (K0); 100 mg/l (K1); 200 mg/l (K2), and 300 mg/l (K3). Observations were made every month variables included plant height, number of leaves, length and width of leaves, number of roots, and length of roots. The results showed that the type and concentration of auxin (Naphthalene Acetic Acid) and (Indole Butyric Acid) interacted to support the growth of leaf length, leaf width, and root length of Dendrobium sp orchids. IBA auxin was more effective in promoting growth and rooting of Dendrobium sp than NAA hormone, the optimal concentration of 200 mg/l until the age of 3 months after acclimatization.